Internationalization of education in China - pedagogical analysis of historical development and political context - Anna Mańkowska (Studia z Teorii Wychowania)
The article concerns the development of internationalization of higher education in China. The paper describes the historical development of higher education and the development of internationalization of higher education, recalling the most important facts. The author points out that the first forms of internationalization took the form of student and scientific international exchanges, and over time, along with the introduction of the country's economic development strategy, the country focus on creating strategic mergers, alliances and international cooperation, which are regulated directly by the PRC (e.g. OBOR) or are transnational (e.g. BRICS), where the Chinese state plays one of the main role. The article is based on the analysis of existing research by Chinese researchers, where the analytical perspective of a researcher from a different culture, participating in the process of internationalization of higher education in the world, is presented.